The Implementation of Maqasid Al-Shariah in Shaykh Yusuf Al-Qardhawi’s Fiqh al-Aqalliyat - Sahidin, Amir; Muhammad Alif Rahmadi, Muhammad Alif Rahmadi (Jurnal Hukum Islam, 2021)
This article aimed to respond Muslim minorities' anxiety in the West, which deals with several dilemmatic choices of daily religious life activity. Muslim minorities are required to obey the teachings of Islam. Still, on the other hand, it contradicts with the reality of how difficult practicing Islamic teachings in Western countries according to the Islamic teachings such in Muslim-majority countries. Therefore, Shaykh Yusuf al-Qardhawi saw the need to initiate fiqh that could guide Muslim minorities in the West to continue to practice Islamic law, although in a slightly different format from prevailing teachings in Muslim-majority countries. This fiqh is popularly known as Fiqh al-Aqalliyat. As initiator, Shaykh Yusuf al-Qardhawi was very concerned about the implementation of maqāṣid al-sharī‘ah. This article used library research. Based on this study, it can be concluded that the implementation of maqāṣid al-sharī‘ah in Shaykh Yusuf al-Qardhawi's Fiqh al-Aqalliyat can be seen from the basis of his arguments, which aims such as the basis of the proposition relying on the law. It is also based on the main source of maqāṣid al-sharī‘ah, the principle of paying attention to universal fiqh rules, etc. Furthermore, we can also consider his fatwas, such as the problem of overseeing the implementation of Friday prayers, the law of inheritance from non-Muslims, christmas compliment to Ahlul Kitab, and establishing Islamic institutions from zakat assets.